Public Financial Support for Commercial Innovation in ECA Countries - Goldberg, Itzhak; Trajtenberg, Manuel; Jaffe, Adam; Muller, Thomas; Sunderland, Julie; Blanco Armas, Enrique (World Bank, Washington, DC, 2012)
Key factors driving self-sustained, long-term economic growth are innovation and technology absorption; these factors are generated from within the economic system, responding to economic incentives. This conceptual framework molds analysis: on the one hand, the view of the centrality of innovation and knowledge creation in the growth process and, on the other hand, the understanding that these are economic factors that may be shaped and influenced by properly designed economic policies. For the purpose of this knowledge brief, innovation can be defined as the development and commercialization of new unproven technologies and untested processes and products, and absorption as the application of existing technologies, processes, and products. The ability of an economy to research and develop new technologies increases its ability to understand and apply existing technologies. Vice versa, the absorption of cutting-edge technology inspires new ideas and innovations.